Hydrogen production by partial oxidation of methane over Co based, Ni and Ru monolithic catalysts - Figen, Halit Eren; Baykara, Sema Z. (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Fossil fuels which supply most of the world energy demand are depletable, and they cause greenhouse gas emissions which eventually lead to global warming and climate change. Hydrogen, a clean and versatile energy carrier, can be converted into useful forms of energy in several ways. Catalytic partial oxidation of methane is a very promising process for hydrogen and synthesis gas production, besides steam reforming of methane, the leading technology. In the present work, catalysts for partial oxidation of methane have been developed and studied in terms of structural properties and chemical performance. For this purpose Co, Co-Ni, Co-Ru, Co-Ni-Ru, and Ni catalysts loaded onto cordierite ceramic monolithic supports were prepared via modified sol-gel-impregnation method. The catalysts were characterized by, SEM-EDS, XRD, BET, and ICP-OES techniques. Activity tests of the catalysts were performed in a tubular reactor at 450 ml/min total flow rate from 600 degrees C to 850 degrees C. Co-Ni-Ru was the most successful catalyst, with selectivity values of 93.10% H-2 and 93.81% CO, and CH4 conversion of 98.71%, and hydrogen production efficiency of 95.89% at 850 degrees C. During the activity tests of this catalyst 2.13% CO2 was present in the product stream. Copyright (c) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen production; Methane; Partial oxidation; CPOM; Catalyst; Monolith support; SYNTHESIS GAS; SUPPORTED METALS; CARBON; SYNGAS; COBALT; FUEL; Chemistry; Electrochemistry; Energy & Fuels